Comparison of different immunosuppressive regimens on skin allograft survival - Chaves, Diva Novy Barbosa; Petroianu, Andy; Alberti, Luiz Ronaldo (Brazilian Journal of Transplantation, 2006)
Purposes: Allograft is one of the major therapeutic options to treat extensive burn victims with insufficient skin donor areas. The present research studied the effects of cyclosporine, as an immunosuppressant model, thalidomide and diclofenac on skin allograft. Methods: Forty-two rabbits were divided into the following groups (n = 6): Group 1 - autografting control; Group 2 - allografting control; Group 3 - allografts under effect of thalidomide (100 mg/kg/day); Group 4 - allografts under effect of sodium diclofenac (2 mg/kg/day); Group 5 - allografts under effect of cyclosporine (10 mg/kg/day); Group 6 - allografts under effect of cyclosporine (5 mg/kg/day); Group 7 - allografts under effect of cyclosporine (5 mg/kg/day) plus thalidomide (100 mg/kg/day). Drugs were given via an orogastric tube one day before the transplant and daily along the postoperative period. The circular total ear skin grafts were changed between the California and White New Zealand rabbits. Results: Cyclosporine 10 mg/kg/day increased the allograft survival, and this effect was comparable to the association of cyclosporine 5 mg/kg/day plus thalidomide 100 mg/kg/day. Thalidomide as an isolated drug and diclofenac had a minimum effect on the average survival of the skin allografts. Conclusion: Thalidomide associated to cyclosporine in a subtherapeutic dose was effective to treat skin allografts.